Posttotalitarna pamięć jako wyzwanie we współczesnej kulturze wschodnioeuropejskiej - Pukhonska, Oksana (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
Contemporary Europe stands before the challenge of rethinking its own experience of totalitarian past with its many blank pages, which are highly important for modern societies. In this case we mostly talk about Soviet totalitarianism. Its ideological rhetoric changed the memory of a large part of Eastern and Central Europe. Ukraine, after the Revolution of Dignity and during the current war in Donbas, tries to prove that that totalitarian memory was illusory and cannot be valid now. The strategies for exposing the crimes of totalitarian regimes are suggested by the texts of contemporary culture, especially literature.